Electroanalytical Determination of Cd(II) and Pb(II) in Bivalve Mollusks using Electrochemically Reduced Graphene Oxide‐based Electrode. Issue 11 (11th July 2019) - Pizarro, Jaime; Segura, Rodrigo; Tapia, Diego; Bollo, Soledad; Sierra‐Rosales, Paulina
Abstract: An electrochemical sensor for the simultaneous determination of Cd(II) and Pb(II) by square wave anodic stripping voltammetry (SWASV) in bivalve mollusks using a glassy carbon electrode modified with electrochemically reduced graphene oxide has been developed. The modified surface was characterized by cyclic voltammetry, high resolution scanning electron microscopy (HR‐SEM), and Raman spectroscopy. The optimum conditions were optimized and a linear range was observed from 15–105 μg L −1 with a limits of detection of 15 μg L −1 for Cd(II) and Pb(II). The methodology was validated and applied in different samples of commercial bivalve mollusks with satisfactory results. The high conductivity and greater surface area of the modifying agent improves the preconcentration capacity of the electrochemical sensor, allowing to develop a simple, rapid and sensitive analysis in the detection of lead and cadmium in marine resources. Abstract :